Lenticulostriate Vasculopathy and Neurodevelopmental Outcomes in Preterm Infants: A Systematic Review - Robinson, Abby; Flibotte, John; Kaplan, Summer L.; DeMauro, Sara B. (American Journal of Perinatology, 2017)
Objective The objective of this study was to perform a systematic review of all studies that report neurodevelopmental outcomes at 12 months' corrected age or later for preterm infants (< 32 weeks) who are diagnosed with lenticulostriate vasculopathy (LSV) on cranial ultrasound.Study Design This is a systematic review.Results We identified 501 unique publications of which 3 met all prespecified eligibility criteria. Neurodevelopmental outcome data were available for 44 preterm infants with LSV. There were mixed results from the studies: the first reported impairments of mental development; the second reported impairments of motor development only; and finally, the third reported that three of three preterm infants with LSV had mild or moderate developmental delay.Conclusion The available results raise some concern for future impairments in preterm infants with LSV, but they are conflicting and inconclusive. There is insufficient evidence about the neurodevelopmental implications of LSV in preterm infants to inform counseling of parents.
Keywords: lenticulostriate vasculopathy; preterm infants; cranial ultrasound; neurodevelopmental outcomes